Anurātapuram Aruḷmiku Katirēcaṉ Ālaya puṉaruttāraṇa makā kumpāpiṣēka niṉaivumalar, 28.04.1980 (Ilaṅkaip Piratēca Apivirutti Intu Camayat Tamiḻ Aluval Amaiccu, 1980)
Volume brought out on the renovation ceremony of the Katirecan Alayam, Shaivite temple at Anuradhapura, Sri Lanka; comprises brief history of the temple and selections from the Tirumurai, Tamil Shaivite devotional literature.